Israel and Palestine : alternative perspectives on statehood - Ehrenberg, John, 1944-; Peled, Yoav (Lanham : Rowman & Littlefield Education, 2016)
This book is designed to introduce American readers to the terms of the discussion of a two-state solution. It features essays by well-known Israeli academics, both Jewish and Palestinian, as well as contributions from non-Israeli citizen Palestinian, and American scholars. It is the first to bring together a wide-range of views and perspectives by influential scholars from various disciplines as well as from activists to bear on a very topical subject with international ramifications.
Overviews -- Facing the music : Israel, Palestine, and the politics of partisan delusions / Stephen Eric Bronner -- Sense of the Nakba : Ari Shavit, Baruch and Zionist claims to territory / Ian S. Lustick -- Israel and the closing of the American Jewish mind / Richard Silverstein -- The root causes of enduring conflict : can Israel and Palestine co-exist? / Jeffry Frieden -- Reclaiming human rights : alternative paths to an Israeli/Palestinian peace / Micheline Ishay and David Kretzmer -- Two states -- Not exactly apartheid : between settler colonialism and military occupation / Honaida Ghanim -- The one-state delusion / Assaf Sharon -- To what extent reconciliation? An analysis of the Geneva accord between Israelis and Palestinians / Yoav Kapshuk -- One homeland, two states : planning alternative spatial relations between Palestine and Israel / Rassem Khamaisi -- The one-state alternative -- The way forward in the Middle East / Horit Herman Peled -- The one-state solution and the Israeli-Palestinian conflict : Palestinian challenges and pro-spects / Leila Farsakh -- A one-state solution? From a "struggle unto death" to "master-slave" dialectics / Raif Zreik -- Past and present perfect of Israel's one-state solution / Moshe Behar -- Confederation -- Towards a shared vision of Israel and Israel/Palestine / Oren Barak -- Neither one nor two : reflections about a shared future in Israel-Palestine / Lev Luis Grinberg -- Between one and two : apartheid or confederation for Israel/Palestine? / Oren Yiftahel -- Beyond traditional sovereignty theory in conflict resolution : lessons from Israel/Palestine / Amal Jamal -- Conclusion : out of the darkness / John Ehrenberg.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
eBooks on EBSCOhost
Keywords: Arab-Israeli conflict -- 1993- -- Peace; Israel -- Politics and government -- 1993-; Palestinian Arabs -- Politics and government -- 1993-; Palestine question (1948-); Conflit israélo-arabe -- 1993- -- Paix; Israël -- Politique et gouvernement -- 1993-; Palestiniens -- Politique et gouvernement -- 1993-; HISTORY -- Middle East -- General; Arab-Israeli conflict -- Peace; Palestinian Arabs -- Politics and government; Politics and government; Israel; Since 1993; Electronic book